DEVELOPMENT OF A MULTI-CRITERION METHODOLOGY FOR ASSESSING COOPERATION BETWEEN FRANCHISING SUBJECTS AND DETERMINING EFFECTIVENESS (Marketing Journal, 2026)
This article develops a multi -criteria methodology for assessing the level of cooperation between franchising entities. It is substantiated that strategic collaboration between franchisors and franchisees should not be limited to legal and financial mechan isms, but must also be evaluated through non -traditional indicators such as service quality, innovation adoption level, and compliance with brand standards. In the study, KPI indicators were identified, their practical relevance was validated through the D elphi expert assessment method, and their weight coefficients were calculated using the AHP method. At the final stage, the Cooperation Strength Index (CCI) was developed and tested on 10 franchising networks. The results revealed significant variations in cooperation levels across networks, highlighted compliance with brand standards as the most influential factor, and confirmed the existence of synergy among KPI indicators. The proposed methodology has practical significance for strategic management of fr anchising systems, strengthening franchisor –franchisee relations, and designing governmental support programs for franchising development.
Keywords: franchising; cooperation; KPI; Delphi; AHP; SERVQUAL; cooperation strength index; brand standards; consulting services; innovation adoption; evaluation methodology; strategic collaboration; franchisor; franchisee